Pengambilan Keputusan Seorang Manager Terhadap Perilaku Karyawan - Rini Wijayaningsih; Kanizah Kanizah; Mutiara Salsabila; Nabila Zahra Octaviany; Sabrina Fitria; Putri Salsabilla R (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research aims to analyze how a manager makes decisions regarding employee behavior in a company. This research uses a qualitative approach with library research methods. The data used is secondary data using sources from books, journal articles, websites and other trusted sources. The data analysis technique used is qualitative data analysis. The research results show that managers and employees must always work together to achieve new goals and contribute to the company. A professional manager will bring success to a company. conversely, if a manager does not understand his job duties and requirements and is unable to complete them, the company will suffer and may experience failure, which will be detrimental to employees or subordinates.